Empirical evidence of the effect of mandatory audit firm rotation on market concentration in South Africa - Dale J. McGregor; Lindela X. Malambe (South African Journal of Economic and Management Sciences)
Background: The audit market in South Africa is dominated by the Big Four audit firms, which decreases competition and may result in reduced productivity, innovation and economic growth.